Incidence of non-cardia gastric cancer among commercially-insured individuals aged 18–64 with chronic atrophic gastritis - Robert J. Huang; Vidhya Balasubramanian; Miranda V. Shum; Hanlee P. Ji; Joo Ha Hwang (PLoS ONE, 2025)
Background Chronic atrophic gastritis (CAG) is a precancerous condition of the gastric mucosa which predisposes to non-cardia gastric cancer (NCGC). The risk for NCGC following diagnosis with CAG has not been described robustly in the United States. Methods We used a commercial claims database (Marketscan, Merative LP) covering over 150 million privately-insured Americans aged 18–64 to create a cohort of individuals diagnosed with CAG. We then followed these individuals for the development of NCGC or to the time of their last clinical encounter. Demographic and clinical characteristics were captured through administrative coding schema, and linked to metropolitan statistical area measures of socioeconomic status. Individual race and ethnicity were not available for this analysis. Findings We analyzed data on 107,835 individuals and recorded 355,591 person-years (p-y) of follow-up. The crude overall incidence of NCGC was 98 per 100,000 p-y. In the fully-adjusted multivariable proportional hazards model, age ≥ 50 (HR 2.20, 95% CI 1.44–3.36), anemia (HR 5.09, 95% CI 3.46–7.50), former or current smoking (HR 1.42, 95% CI 1.11–1.81) and family history (HR 1.44, 95% CI 1.05–1.99) were individual-level factors associated with increased risk. Conclusions We present one of the first estimates of NCGC risk following CAG diagnosis in an American population, and highlight risk factors for cancer progression. These data may help to guide future risk prevention strategies, such as endoscopic surveillance, in the United States.